Examining Language Development Quality in Early Childhood Education: A Systematic Review of Assessment and Monitoring Frameworks in Indonesia - Sinta Maulida Hapsari; Nindya Alifia Tittandi; Octavian Dwi Tanto (Salus Cultura)
The quality of language development in early childhood education (PAUD) plays a crucial role in preparing children for primary education and supporting their overall cognitive growth. However, despite the existence of various assessment practices across Indonesia, inconsistencies remain in the use of tools, monitoring frameworks, and their practical application within PAUD institutions. This study aims to critically analyze the types of assessment instruments and monitoring frameworks used to evaluate language development in Indonesian PAUD contexts through a systematic review. To achieve this objective, the study applied a systematic review method guided by the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) protocol, ensuring a structured and transparent process in identifying, selecting, and synthesizing relevant studies. A total of 20 empirical studies and literature reviews published between 2019 and 2024 were selected from databases including SINTA, GARUDA, DOAJ, Google Scholar and Scopus. The findings reveal that observational checklists, anecdotal records, and portfolio assessments are the most commonly used methods, while the use of digital tools—such as e-portfolios and language development applications—remains limited and underutilized. Most monitoring frameworks are aligned with the 2013 National Curriculum and Ministerial Regulation No. 137 of 2014, although implementation gaps persist due to variations in teacher competence, institutional capacity, and technological infrastructure. This review underscores the urgent need for a standardized, culturally relevant, and technology-integrated system for assessing language development in early childhood education. Enhancing teacher assessment literacy, promoting the integration of digital solutions, and improving policy coherence are recommended to advance the effectiveness and equity of language monitoring practices in Indonesia's PAUD sector.